Employment trajectories among individuals with opioid use disorder: Can evidence-based treatment improve outcomes? - Mary A. Burke; Riley Sullivan; Katherine Grace Carman; Hefei Wen; J. Frank Wharam; Hao Yu (Federal Reserve Bank of Boston, 2022)
Using administrative records of Medicaid enrollees in Rhode Island that link their health-care information with their payroll employment records, this paper produces new stylized facts concerning the association between opioid use disorder (OUD) and employment and inquires as to whether treatment with FDA-approved medications might boost the job-finding rates of OUD patients. We find that individuals diagnosed with OUD are less likely to be employed compared with other Medicaid enrollees, that their employment tends to be more intermittent, and that they face increased job-separation risk following their initial diagnosis. In addition, commencing treatment with buprenorphine is associated with an increased job-finding rate among nonemployed OUD patients, while commencing methadone treatment is not associated with any significant change in job-finding rates. The job-separation rate and job-finding rate results are based on Cox proportional hazard regressions that control for numerous potential confounding factors. The paper discusses a variety of causal and noncausal explanations for these results in addition to their potential policy implications.
Keywords: J21; J24; I18; I12; 330; Opioid use disorder; employment; job-finding rate; buprenorphine; methadone; Medicaid; Rhode Island